Est miser nemo nisi comparatus (Sen. Tr. 1023) o come essere (in)felici senza esserlo - Casamento, Alfredo (Lucius Annaeus Seneca, 2021)
This article deals with the presence of unhappiness and painsharing in Seneca’s Troades and demonstrates the presence of a common thread that runs through the whole drama, which finds an exceptional relief in the fourth choral interlude. The lot of the prisoners allows for a painful meditation on the imminent exile and on the importance of sharing suffering.